De-Globalization: Fact or Fiction? - Jordaan, André (Latin American Journal of Trade Policy, 2022)
Globalization conveys the widely accepted idea that we are living in a border-less world. According to this view, no notice is taken of distance or national policy anymore, dictated by global markets. However, the concept of de-globalization is starting to appear in literature with evidence of a growing awareness. It seems that there is a transition from globalization and trade integration to economic nationalism or de-globalization. Recent data suggests that the level of de-globalization is on the increase globally. This phenomenon may cause vulnerable countries to reassess their position in the global trade environment as conventional trade agreements and partners may be jeopardized. The COVID-19 pandemic has spilled over to the global economy triggering a massive decline in economic activity, mainly because of government mandated lockdowns and general mobility restrictions. This has also had a dramatic effect on the functioning of global value chains, increasing the visible threat of de-globalization. Recent trends associated with the move towards de-globalization among G-20 countries and concomitant risks are also explored.